المقاصد الشرعية للأحكام الفقهية المتعلقة بالمرأة في الحياة الزوجية = The Shariah’s Maqasid of fiqh rulings related to married women - Ghalia, Bouhedda; Chourana, Mohamed; Bensayah, Sana (IIUM Press, International Islamic University Malaysia, 2018)
يهدف البحث إلى إبراز وحصر أهم الأحكام الفقهية المتعلقة بالمرأة الزوج داخل الأسرة وبيان مقاصدها، والتأكيد على رعاية الإسلام ورفقه بالمرأة من خلال الضمانات وتوضيح التدابير التي أحاطها بها عند منحها حقوقها وتشريع أحكامها الفقهية في الأسرة، اعتمد الباحثان في هذه الدراسة على منهج علمي سارا عليه في بحثهما وهو في أغلبه منهج استقرائي تحليلي، أمّا المنهج الاستقرائي فقد اعتُمد في استقراء الآثار العلمية المرتبطة بأحكام المرأة الفقهية المتعلقة بالأسرة، و أمّا المنهج التحليلي فقد اعتُمد في دراسة الفروع الفقهية دراسة تحليلية وعرضها للمناقشة لتستبين من خلالها المقاصد الشرعية لها، وممّا تقرر في نتائج البحث أنّ قيام المرأة بدورها داخل الأسرة هو حفظ لمقاصد الأسرة وبالتالي حفظ للمقاصد الشرعية الضرورية كونها هي محضن النسل، وأن العلم بمقاصد الأحكام الفقهية الخاصة بالمرأة داخل الأسرة ، يحقق كثيراً من المصالح ويحفظ الأسرة ويديم رابطتها، ويدرأ عنها العديد من المفاسد. ********************************************************* The current study embarked on highlighting and summarizing the most important jurisprudential provisions regarding women (wives) within the family and the statement of her intentions. The emphasis on the care of Islam and its attachment to women through guarantees and clarifying the measures that surrounded them when granting rights and legislation of jurisprudence in the family, In this study, the researcher adopted a scientific approach, which is mostly an inductive analytical method, Furthermore, the inductive approach was employed to extrapolate the scientific implications associated with women's jurisprudence and related to family, The analytical approach has been adopted in this study for the jurisprudence branches (analytical study) and discussed to further determine the purposes of Islamic legitimacy, It is decided in the results of the research that the role of women within the family is the preservation of the purposes of the family, thus the preservation Maqasid of shariah as due to being the incubator of the reproduction. Also having the knowledge of the purposes of the provisions of the Fiqh that related to women within the family will keep the family maintained and will protect it from the evils.